Pengaruh Model Pembelajaran Think Talk Write Terhadap Kemampuan Menulis Karangan Deskripsi Siswa Kelas IV SDN 101732 - Saragih , Jheni Yusuf; Girsang, Mei Lyna; Indryani, Novinda (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2022)
The purpose of this study is to determine the effect of the Think Talk Write learning model on student’s ability in writing descriptive essays of Fourth grade students at SDN 101732. This research was an experimental study using Quasi – experimental one group Pretest Posttest design with quantitative approach. Sample of this study were all the students of Fourth grade SDN 101732 totaling 18 students and sample technique is using Total Sampling technique. The data collection technique was using test and documentation and the research data was analyzed using SPPS 22. Based on the results of the study, it was found that the Pretest result were 67.78 and increased to 88.06 in Posttest. So it can be concluded that Think Talk Write learning model affect the student ability in writing descriptive essays of Fourth grade students at SDN 101732.